Remoção dos corantes têxteis C.I. Reactive Blue 203 e C.I. Reactive Red 195 mediante o uso de bagaço de maçã como adsorvente - Marin, Sandra Liliana Albornoz (2015)
The textile industry has a big environmental impact because consume a lot of water, and use different chemical organic products like dyes. There are different methods for treatment of textile effluents one of those is adsorption. Using agroindustrial residues like adsorbents is an alternative for decontamination effluents by dyes. Therefore, this present work aimed to evaluate agroindustrial residue apple pomace of Fuji variety, that proceed of production of juices, like alternative adsorbent for the removal textile dyes C.I. Reactive Blue 203 and C.I. Reactive Red 195 in aqueous synthetic medium. The adsorbent characteristics showed that apple pomace present 89.36% of humidity and 35,64% of crude fiber. and 52,72% of C. The pH (pzc) is 3,5, and its surface prevails sites acids. In infrared spectroscopy it was observed the presence of the major functional groups (–OH), (–NH), (CH2), (–CO), (–C–O–). In scanning electron microscopy of the surface morphology of the apple pomace was found to be porous and determining the textural features indicated a surface area of 2,088 (m2.g-1) to 0,125 mm particle size. From the results of the experimental design 23 can optimize the process of adsorption of for both dyes by apple pomace, setting the independent variables with significant influence (pH of 2.0 and particle size of the adsorbent 0.125 mm). In the kinetic study the equilibrium time for Reactive Blue 203 was 420 minutes and for Reactive Red 195 was 180 minutes and for both dyes mathematical adjustment was to model the pseudo-second order. The equilibrium isotherms were tested by the models adsorption isotherms of Langmuir, Freundlich, Dubinin-Raduskevich and BET, the last being more suitable for the description of the process. The thermodynamic parameters were determined at different ranges of temperature, in which negative values of ΔG° means the spontaneity in the adsorption process for both dyes and negative values for ΔH° for adsorption process of Reactive Blue 203 suggest the exothermic nature However the adsorption to the dye Reactive Red 195 ΔH° positive values suggest its endothermic nature. The values for ΔH° and the Ea for the adsorption of the two dyes in apple pomace show that they are of the same order of magnitude as the heat and the activation energy of chemisorption. The apple pomace was highly favorable for the adsorption of the dye Reactive Blue 203 and Reactive Red 195.